2021
DOI: 10.2147/jir.s318009
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Bioinformatic Strategies with Real-World Data to Infer Distinctive Immunocyte Infiltration Landscape and Immunologically Relevant Transcriptome Fingerprints in Ossification of Ligamentum Flavum

Abstract: Purpose Ossification of the ligamentum flavum (OLF) is a multifactorial disease characterized by an insidious and debilitating process of abnormal bone formation in ligamentum tissues. However, its definite pathogenesis has not been fully elucidated. Potential links between the immune system and various forms of heterotopic ossification have been discussed for many years, whereas no research investigated the immune effects on the initiation and development of OLF. Therefore, we attempt to shed lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The role of lncRNAs has been identified in diverse biological processes, including cell proliferation, apoptosis, and tumorigenesis [ 9 , 10 ]. LncRNAs have also been associated with musculoskeletal diseases, such as osteoarthritis [ 11 ], intervertebral disc degeneration [ 12 ], and Ossification of the ligamentum flavum [ 13 ]. lncRNAs are also involved in the pathological process of fibrosis of the lung [ 14 , 15 ], liver [ 16 , 17 ], kidney [ 18 , 19 ], and heart [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of lncRNAs has been identified in diverse biological processes, including cell proliferation, apoptosis, and tumorigenesis [ 9 , 10 ]. LncRNAs have also been associated with musculoskeletal diseases, such as osteoarthritis [ 11 ], intervertebral disc degeneration [ 12 ], and Ossification of the ligamentum flavum [ 13 ]. lncRNAs are also involved in the pathological process of fibrosis of the lung [ 14 , 15 ], liver [ 16 , 17 ], kidney [ 18 , 19 ], and heart [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research has identified 10 OLF-related and immune-related differentially expressed genes (OIDEGs) ( 20 ). Eleven ORDEGs, OIDEGs, TNF signaling-enriched DEGs (TSDEGs), and immune response-enriched DEGs (IMDEGs) were overlapped to obtain SOCS3 as the core gene ( Figure 7D ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that the population with obesity or diabetes were more likely to suffer from the OLF, which indicated that metabolic disorder might play important roles in the pathogenesis of OLF. 3 , 10 , 14 , 18 Some bioinformatic analyses were conducted to investigate the role of ceRNA network or immunity abnormality in the onset and development of OLF, 31 , 42 however, no study was especially conducted to determine the role of metabolic disorder in the pathogenesis of OLF with strict bioinformatic algorithms. In the current study, we firstly observed the difference of metabolism score between OLF tissues and normal LF tissues, which presented that metabolic disorder might be an important etiological factor for OLF.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Zhang et al analyzed the immunocyte infiltration landscape, and constructed an immunoregulatory network between the immunocytes and immune‐related genes in OLF. 31 However, the relationship between metabolic disorder and immunity abnormality in OLF has not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation